Impact of the Plastic Deformation Microstructure on the Corrosive Resistance of Metallic Materials – The State of the Art and the Effect of Microstructure Refinement on the Example of the 2000 Series Aluminum Alloy - M.M. Lachowicz (Archives of Metallurgy and Materials)
The article discusses the role of the microstructure formed through plastic deformation in the corrosion resistance of metallic materials. Additionally, a review of the existing knowledge in this area is conducted. In particular, the role of the refinement of intermetallic phases is emphasized. For that purpose, investigations of as-cast aluminum alloy, as well as after plastic deformation, from the 2000 series have been performed. Metallographic tests of the examined materials have been carried out, and electrochemical tests as well as SEM examinations of the surface after the corrosion tests have been conducted. It has been documented that the presence of large precipitates existing at distances typical of as-cast alloys favours intensive corrosion. In turn, a significant amount of fine-dispersive precipitates at the initial stage of corrosion can work as a barrier counteracting the corrosion processes.